Wikipedia2Onto— Building Concept Ontology Automatically, Experimenting with Web Image Retrieval - Wang, H.; Jiang, X.; Chia, L.-T.; Tan, A.-H. (Informatica)
Wikipedia2Onto— Building Concept Ontology Automatically, Experimenting with Web Image Retrieval